2017
DOI: 10.1136/bmjopen-2016-015281
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of the Data-driven Quality Improvement in Primary Care (DQIP) trial: case study evaluation of adoption and maintenance of a complex intervention to reduce high-risk primary care prescribing

Abstract: ObjectiveTo explore how different practices responded to the Data-driven Quality Improvement in Primary Care (DQIP) intervention in terms of their adoption of the work, reorganisation to deliver the intended change in care to patients, and whether implementation was sustained over time.DesignMixed-methods parallel process evaluation of a cluster trial, reporting the comparative case study of purposively selected practices.SettingTen (30%) primary care practices participating in the trial from Scotland, UK.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 23 publications
4
35
0
Order By: Relevance
“…Both this network and the dashboard allowed the pharmacists to utilise it for medication safety activities. A similar intervention to improve prescribing safety in primary care, which provided electronic feedback but did not involve pharmacists, found variations in implementation and differences in practice engagement, and that collective engagement within practices, particularly from clinicians, led to more successful implementation [44]. This variation might also be explained in that unlike the previous PINCER trial [11,16] pharmacists in the SMASH intervention stayed with the practices beyond a three-month intervention period.…”
Section: Discussionmentioning
confidence: 89%
“…Both this network and the dashboard allowed the pharmacists to utilise it for medication safety activities. A similar intervention to improve prescribing safety in primary care, which provided electronic feedback but did not involve pharmacists, found variations in implementation and differences in practice engagement, and that collective engagement within practices, particularly from clinicians, led to more successful implementation [44]. This variation might also be explained in that unlike the previous PINCER trial [11,16] pharmacists in the SMASH intervention stayed with the practices beyond a three-month intervention period.…”
Section: Discussionmentioning
confidence: 89%
“…This distinction matters because it is important to avoid discarding a potentially effective intervention that was poorly implemented 10 29 30. Implementation difficulties and deficiencies are not infrequently identified in effectiveness evaluations of complex healthcare delivery interventions31–34 but are not always elucidated 20 35. In this study, we found evidence of a degree of implementation failure and, in addition to identifying poorly implemented components, we have considered reasons for poor implementation and whether they are modifiable.…”
Section: Discussionmentioning
confidence: 89%
“…Studies of earlier interventions to improve prescribing in primary care have reported variations in engagement. [ 39 , 40 ] and have seen differences in roles with some health professionals utilising technology and others rejecting it. [ 44 ] In the present study there were positive outcomes from the differences in roles since the intervention allowed pharmacists to demonstrate their professional skills through the use of the system and develop the role of clinical pharmacy in general practice.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization Process Theory (NPT) [ 35 38 ] can highlight how an intervention is integrated and adopted into routine practice. NPT has previously been used to evaluate prescribing safety interventions in primary care [ 39 40 ], and has utility in examining how individuals and groups understand the intervention through processes of sense-making and how they work to enable the intervention to happen. [ 35 38 ] Interventions become part of everyday practice only through the work that people, individually or in groups, undertake.…”
Section: Methodsmentioning
confidence: 99%